A high-entropy sulfide electrocatalyst, modified battery separator and applications thereof in lithium-sulfur batteries
Patent Information
- Application Number
- CN202410489275.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-22
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-04-22
AI Technical Summary
金属硫化物由于具有较高的导电性和力学稳定性等优势为改性锂硫电池隔膜体系开辟了广阔的前景,但由于金属硫化物活性位点种类单一,催化效果有限等问题,因此金属硫化物改性隔膜对锂硫电池的提升有限
[0038]1、本发明电催化剂制备简单、成本低、催化剂结构稳定、催化性能优异。
Smart Images

Figure CN118454696B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a high-entropy sulfide electrocatalyst, a modified battery separator containing the high-entropy sulfide electrocatalyst, and its application in lithium-sulfur batteries, belonging to the field of battery material technology. Background Technology
[0002] With the continuous development of portable electronic devices and electric vehicles, lithium-ion batteries, due to their limited theoretical capacity and high cost, are unable to meet the ever-increasing energy storage demands. Therefore, the search for lithium-ion rechargeable batteries with good cycle performance, high energy density, and low cost has become a research hotspot. Among them, lithium-sulfur (Li-S) batteries, due to their high theoretical specific capacity (1675 mAh g⁻¹), are particularly promising. -1 The lithium-sulfur battery has attracted widespread attention due to its abundant sulfur resources and environmental friendliness. However, the practical application of lithium-sulfur batteries is still hindered by several challenges: (1) the inherent insulation of S and Li2S; (2) the "shuttle effect" of polysulfide intermediates (soluble polysulfides migrate from the cathode to the anode, reducing sulfur utilization and corroding lithium metal); (3) the slow reaction kinetics between polysulfides (LiPSs) and Li2S, resulting in poor electrochemical kinetics of sulfur in lithium-sulfur batteries.
[0003] As a crucial component of lithium-sulfur batteries, the separator primarily functions as an electronic insulator to prevent internal short circuits. Commercial separators are typically polymer membranes (PP, PE, etc.) containing numerous micropores, with pore sizes much larger than those of polysulfides. This allows soluble polysulfides to easily shuttle freely through the micropores, leading to capacity loss and other issues. Therefore, it is necessary to modify lithium-sulfur battery separators to effectively adsorb lithium polysulfides and lower the activation energy of the reaction, thereby suppressing the shuttle effect and accelerating reaction kinetics, thus improving the capacity and cycle stability of lithium-sulfur batteries. Metal sulfides, due to their high conductivity and mechanical stability, have opened up broad prospects for modified lithium-sulfur battery separator systems. However, due to the limited variety of active sites and limited catalytic effects of metal sulfides, the improvement of lithium-sulfur battery performance by metal sulfide-modified separators is limited. To further improve the catalytic efficiency of metal sulfide catalysts, multiple metals can be doped into the sulfide system. Researchers have doped two elements to form binary sulfides for use in modifying the separator of lithium-sulfur batteries. Due to the increase in active sites, the performance of lithium-sulfur batteries has been improved. However, the two active components have too few active sites to meet the requirements for the adsorption and catalysis of polysulfides. Therefore, the problem of poor cycle stability caused by the shuttle effect in lithium-sulfur batteries has not been well solved. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing a high-entropy sulfide electrocatalyst and the obtained high-entropy sulfide electrocatalyst. The electrocatalyst is prepared by a glycerol-assisted self-templating method. By doping with multiple metal elements, it has multiple active sites. The synergistic effect between multiple active components enables the modified membrane of the high-entropy sulfide electrocatalyst to effectively resist polysulfides, accelerate the redox reaction kinetics of sulfur, and suppress the "shuttle effect" of polysulfides.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a high-entropy sulfide electrocatalyst, the method comprising the following steps:
[0007] (1) Add at least 5 transition metal salts to a mixture of glycerol and solvent, stir until homogeneous, and then subject the resulting mixture to a solvothermal reaction. After the reaction, collect the product to obtain a high-entropy sulfide precursor.
[0008] (2) Mix the high-entropy sulfide precursor, thioacetamide and solvent, stir to obtain a suspension, carry out a solvothermal reaction of the suspension, and then collect the product to obtain the high-entropy sulfide electrocatalyst.
[0009] Furthermore, in step (1), the transition metal can be selected from transition metals such as Fe, Co, Ni, Zn, Cu, Mn, and V. The salt of the transition metal is a soluble salt of the transition metal, preferably a chloride or nitrate of the transition metal. For example, Fe salt can be ferric nitrate, Co salt can be cobalt nitrate, Ni salt can be nickel nitrate, Mn salt can be manganese chloride, Zn salt can be zinc nitrate, V salt can be vanadium chloride, and Cu salt can be copper nitrate.
[0010] Furthermore, in step (1), the transition metal salts are at least 5 types, thereby forming high-entropy sulfides. The transition metal salts can be 5, 6, 7, 8, 9, etc., preferably 5-7 types, and more preferably 5 types.
[0011] Preferably, in step (1), the transition metal salt is a salt of one of the five transition metals: Fe, Co, Ni, Zn, and Mn.
[0012] Furthermore, in step (1), the molar ratio between the transition metal salts is between 1:1 and 1:1.3, and preferably, the transition metal salts are added in equimolar amounts. Preferably, the transition metal salts are Fe salts, Co salts, Ni salts, Zn salts, and Mn salts in equimolar amounts.
[0013] Furthermore, in step (1), glycerol is used as a template. The addition of glycerol has two functions: first, glycerol acts as a template agent, enabling the final electrocatalyst to be regularly spherical; second, glycerol enables the metal elements to be evenly distributed in the electrocatalyst. The molar ratio of glycerol to the total amount of transition metal salt is 50-60:1, for example, 50:1, 51:1, 52:1, 53:1, 54:1, 55:1, 56:1, 57:1, 58:1, 59:1, 60:1.
[0014] Furthermore, in step (1), the solvent serves to provide a reaction medium and ensure uniform mixing of the components. The solvent can be isopropanol, ethanol, etc. The amount of solvent used can be selected according to actual needs and is not particularly required.
[0015] Furthermore, in step (1), after the transition metal salt, glycerol and solvent are mixed, they are stirred at room temperature for 35-45 min, for example 35 min, 40 min, 45 min.
[0016] Furthermore, in step (1), the solvothermal reaction is carried out in a reaction vessel. The solvothermal reaction temperature is 170–200°C, for example, 170°C, 180°C, 190°C, or 200°C. The reaction time is generally 17–20 hours, for example, 17 hours, 18 hours, 19 hours, or 20 hours. Preferably, the reaction temperature is 180°C and the reaction time is 18 hours.
[0017] Further, in step (1), after the solvothermal reaction is completed, the sample is centrifuged, washed, and dried to obtain a high-entropy sulfide precursor. Washing is performed with water, and the drying temperature is 60-80℃, for example, 60℃, 70℃, or 80℃, preferably 70℃. The drying time is generally 9-13 hours, for example, 9h, 10h, 11h, 12h, or 13h, preferably 12h.
[0018] Furthermore, in step (2), the mass ratio of the high-entropy sulfide precursor to thioacetamide is 3:(4-6), for example 3:4, 3:5, 3:6, preferably 3:4.
[0019] Furthermore, in step (2), the solvent serves to provide a reaction medium and ensure uniform mixing of the components. The solvent can be ethanol, deionized water, etc. The amount of solvent used can be selected according to actual needs and is not particularly required.
[0020] Furthermore, in step (2), after the high-entropy sulfide precursor, thioacetamide and solvent are mixed, they are stirred at room temperature for 25-40 min, for example 25 min, 30 min, 35 min and 40 min.
[0021] Furthermore, in step (2), the solvothermal reaction is carried out in a reaction vessel. The solvothermal reaction in step (1) can be referred to as the first solvothermal reaction, and the solvothermal reaction in step (2) can be referred to as the second solvothermal reaction. The reaction temperature of the second solvothermal reaction is 150-170℃, for example, 150℃, 160℃, or 170℃. The reaction time is generally 17-20h, for example, 17h, 18h, 19h, or 20h. Preferably, the reaction temperature is 160℃ and the reaction time is 18h.
[0022] Furthermore, in step (2), the drying temperature is 60-80℃, for example, 60℃, 70℃, or 80℃. The drying time is 9-13h, for example, 9h, 10h, 11h, 12h, or 13h. Preferably, the drying temperature is 70℃ and the drying time is 12h.
[0023] Furthermore, in step (2), after the solvothermal reaction is completed, the sample is centrifuged, washed, and dried to obtain a high-entropy sulfide electrocatalyst. Washing is performed using water, and the drying temperature is 60-80℃, for example, 60℃, 70℃, or 80℃, preferably 70℃. The drying time is generally 9-13 hours, for example, 9h, 10h, 11h, 12h, or 13h, preferably 12h.
[0024] The high-entropy sulfide electrocatalyst prepared according to the method of the present invention is spherical, wherein each metal element is uniformly doped. The synergistic effect between multiple active components enables the high-entropy sulfide electrocatalyst to effectively resist polysulfides, accelerate the redox reaction kinetics of sulfur, and suppress the "shuttle effect" of polysulfides.
[0025] The present invention also provides a modified battery separator, the battery separator comprising a battery separator body, wherein an electrocatalyst layer is coated on the battery separator body, the electrocatalyst layer containing the high-entropy sulfide electrocatalyst described in the present invention.
[0026] Furthermore, the battery separator is coated with a high-entropy sulfide electrocatalyst, which can suppress the shuttle effect of polysulfides and improve the battery's capacity and cycle stability.
[0027] Furthermore, the battery separator body is a polymer separator commonly used in existing batteries, such as polyethylene (PE) separator, polypropylene (PP) separator, etc.
[0028] Furthermore, the electrocatalyst layer is coated on the upper or lower surface of the battery separator.
[0029] Furthermore, the electrocatalyst layer is composed of a high-entropy sulfide electrocatalyst and a binder, with a mass ratio of high-entropy sulfide electrocatalyst to binder of 4-9:1, for example, 4:1, 5:1, 6:1, 7:1, 8:1, or 9:1. The binder can be a lithium-sulfur battery-specific adhesive, such as LA133 or polytetrafluoroethylene.
[0030] Furthermore, the coating thickness of the electrocatalyst layer on the battery separator body is 5 to 50 μm, for example 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, preferably 25 μm.
[0031] Furthermore, the modified battery separator is prepared by: mixing the high-entropy sulfide electrocatalyst and the binder in a certain proportion to form a slurry, coating the slurry onto the surface of the battery separator body, and drying it to obtain the modified battery separator.
[0032] The present invention also provides the application of the above-mentioned high-entropy sulfide electrocatalyst or modified battery separator in lithium-sulfur batteries.
[0033] In one specific embodiment of the present invention, a method for assembling a lithium-sulfur battery is also provided, which specifically includes the following steps:
[0034] (1) Grind sulfur powder and BP2000 carbon black in a mass percentage ratio of 70-80%: 30-20% for 30-40 minutes, and then put them in an oven at 155℃ for 12 hours to obtain sulfur-carbon cathode material.
[0035] (2) After mixing and grinding the sulfur-carbon cathode material, conductive carbon, and LA133 binder in a mass ratio of (7-8):(2-1):1, the slurry is coated onto the surface of the carbon-coated aluminum foil, dried under vacuum at 60°C, and then cut into round pieces with a diameter of 8 mm to obtain the sulfur-carbon electrode sheet.
[0036] (3) Assemble a button cell in a glove box filled with argon gas. The positive electrode is a sulfur-carbon electrode, the negative electrode is metallic lithium, and the separator is a battery separator modified with the high-entropy sulfide electrocatalyst of this invention. The electrolyte consists of 1 mol / L lithium bis(trifluoromethanesulfonyl)imide, 1-2 wt% lithium nitrate, and the remainder is solvent. The solvent is a mixture of 1,3-dioxolane (DOL) and dimethyl ethylene glycol (DME) in a volume ratio of 1:1.
[0037] This invention prepares a high-entropy sulfide electrocatalyst via a glycerol-assisted self-templating method and uses this electrocatalyst to modify a battery separator. The electrocatalyst of this invention, by doping with multiple transition metal elements, possesses multiple active sites. The synergistic effect among the multiple active components enables the high-entropy sulfide electrocatalyst-modified separator to effectively resist polysulfides, accelerate the redox reaction kinetics of sulfur, and suppress the "shuttle effect" of polysulfides. The high-entropy sulfide electrocatalyst-modified separator prepared by this invention exhibits excellent mechanical properties, and the assembled lithium-sulfur battery demonstrates high discharge specific capacity (1341.5 mAh / g, 0.2C) and excellent cycle stability, showing broad application prospects in lithium-sulfur batteries. Compared with existing technologies, this invention has the following beneficial effects:
[0038] 1. The electrocatalyst of this invention is simple to prepare, low in cost, has a stable catalyst structure, and excellent catalytic performance.
[0039] 2. The high-entropy sulfide electrocatalyst of the modified membrane of the present invention is prepared by glycerol-assisted self-templating method, wherein each element is uniformly doped and different active components have synergistic effects, which can effectively resist polysulfides and accelerate the redox kinetics of sulfur.
[0040] 3. The high-entropy sulfide catalyst-modified battery separator prepared by this invention has excellent mechanical properties and stability, and no powder shedding occurs after bending and folding.
[0041] 4. The preparation method of this invention is simple, the selected active components are all transition metal elements, and the required raw materials are widely available, which greatly reduces the production cost.
[0042] 5. The high-entropy sulfide electrocatalyst modified membrane obtained in this invention is used in lithium-sulfur batteries, and the assembled lithium-sulfur batteries have excellent discharge specific capacity and strong long-term cycle stability. Attached Figure Description
[0043] Figure 1 The image shows the X-ray diffraction (XRD) pattern of the high-entropy sulfide electrocatalyst ((FeCoNiMnZn)3S4) prepared in Example 1.
[0044] Figure 2 The images show scanning electron microscopy (SEM) and energy-scattering X-ray spectroscopy (EDS) spectra of the high-entropy sulfide electrocatalyst ((FeCoNiMnZn)3S4) prepared in Example 1.
[0045] Figure 3 This is a photograph of the folding and bending test of the high-entropy sulfide electrocatalyst modified battery separator ((FeCoNiMnZn)3S4 / PP) prepared in Example 1. Figure 4The discharge specific capacity of the lithium-sulfur battery using the (FeCoNiMnZn)3S4 / PP separator of Application Example 1 at discharge rates of 0.3C, 0.4C, 0.5C, 1C, and 2C is given. Detailed Implementation
[0046] The present invention will be further described below through specific embodiments. However, it should be understood that the following description is merely exemplary and does not limit the scope of protection of the present invention.
[0047] Example 1
[0048] The method for preparing high-entropy sulfide electrocatalysts includes:
[0049] 1. Add 0.202g Fe(NO3)3·9H2O, 0.1487g Zn(NO3)2·6H2O, 0.1456g Co(NO3)2·6H2O, 0.145g Ni(NO3)2·6H2O and 0.063g MnCl2 to a beaker, then add 80ml isopropanol and 10ml glycerol, stir at room temperature for 40min, then place in a reaction vessel and react at 180℃ for 18h. After the reaction is completed, centrifuge and wash the sample, then dry it in a 70℃ oven for 12h to obtain the high-entropy sulfide precursor.
[0050] 2. Weigh 30 mg of high-entropy sulfide precursor and 40 mg of thioacetamide, dissolve them in 20 ml of anhydrous ethanol, stir at room temperature for 30 min on a magnetic stirrer, then put them into a reaction vessel and react at 160 °C for 18 h. After the reaction is completed, centrifuge and wash the sample, and dry it in a 70 °C oven for 12 h to obtain the high-entropy sulfide electrocatalyst ((FeCoNiZnMn)3S4).
[0051] like Figure 1 As shown, the high-entropy sulfide electrocatalyst was characterized using X-ray diffraction (XRD). Figure 1 As can be seen, the high-entropy sulfide exhibits distinct diffraction peaks at 2θ = 16.3°, 26.7°, 31.5°, 38.1°, 47.2°, 50.2°, and 55.1°, corresponding to the (111), (220), (311), (400), (422), (511), and (440) crystal planes of Co3S4 (JCPDF No. 47-1738), respectively. Furthermore, the synthesized (FeCoNiZnMn)3S4 shows no diffraction peaks from other secondary or impurity phases, indicating that the synthesized sample is a single phase.
[0052] from Figure 2It can be seen that the high-entropy sulfide ((FeCoNiZnMn)3S4) has a spherical morphology. This structure is conducive to exposing more active sites, promoting the adsorption and catalytic conversion of polysulfides. Furthermore, the EDS shows that the doped elements are uniformly distributed.
[0053] Example 2
[0054] The high-entropy sulfide electrocatalyst was prepared according to the method in Example 1, except that the amount of thioacetamide used was 50 mg.
[0055] Example 3
[0056] A high-entropy sulfide electrocatalyst ((FeCoNiZnV)3S4) was prepared according to the method in Example 1, except that 0.063 g of MnCl2 was replaced with 0.0786 g of VCl3.
[0057] Example 4
[0058] The high-entropy sulfide electrocatalyst ((FeCoNiMnV)3S4) was prepared according to the method in Example 1, except that 0.1487 g Zn(NO3)2·6H2O was replaced with 0.0786 g VCl3.
[0059] Example 5
[0060] The method for preparing high-entropy sulfide electrocatalysts includes:
[0061] 1. Add 0.168g Fe(NO3)3·9H2O, 0.121g Co(NO3)2·6H2O, 0.121g Ni(NO3)2·6H2O, 0.0525g MnCl2, 0.124g Zn(NO3)2·6H2O and 0.0655g VCl3 to a beaker, then add 80ml isopropanol and 10ml glycerol, stir at room temperature for 40min, then place in a reaction vessel and react at 180℃ for 18h. After the reaction is completed, centrifuge and wash the sample, then dry it in a 70℃ oven for 12h to obtain the high-entropy sulfide precursor.
[0062] 2. Weigh 30 mg of high-entropy sulfide precursor and 40 mg of thioacetamide, dissolve them in 20 ml of anhydrous ethanol, stir at room temperature for 30 min on a magnetic stirrer, then put them into a reaction vessel and react at 160 °C for 18 h. After the reaction is completed, centrifuge and wash the sample, and dry it in a 70 °C oven for 12 h to obtain the high-entropy sulfide electrocatalyst ((FeCoNiMnZnV)3S4).
[0063] Example 6
[0064] The method for preparing high-entropy sulfide electrocatalysts includes:
[0065] 1. Add 0.144g Fe(NO3)3·9H2O, 0.104g Co(NO3)2·6H2O, 0.104g Ni(NO3)2·6H2O, 0.045g MnCl2, 0.106g Zn(NO3)2·6H2O, 0.089g Cu(NO3)2·3H2O and 0.0561g VCl3 to a beaker, then add 80ml isopropanol and 10ml glycerol, stir at room temperature for 40min, then place in a reaction vessel and react at 180℃ for 18h. After the reaction is completed, centrifuge and wash the sample, then dry it in a 70℃ oven for 12h to obtain the high-entropy sulfide precursor.
[0066] 2. Weigh 30 mg of high-entropy sulfide precursor and 40 mg of thioacetamide, dissolve them in 20 ml of anhydrous ethanol, stir at room temperature for 30 min on a magnetic stirrer, then put them into a reaction vessel and react at 160 °C for 18 h. After the reaction is completed, centrifuge and wash the sample, and dry it in a 70 °C oven for 12 h to obtain the high-entropy sulfide electrocatalyst ((FeCoNiMnZnVCu)3S4).
[0067] Comparative Example 1
[0068] 1. Add 0.202g Fe(NO3)3·9H2O, 0.1487g Zn(NO3)2·6H2O, 0.1456g Co(NO3)2·6H2O, 0.145g Ni(NO3)2·6H2O and 0.063g MnCl2 to a beaker, then add 32mL N,N-dimethylformamide (DMF), 2mL ethanol, 2mL deionized water and 2mmol terephthalic acid (PTA) solution. Stir at room temperature for 40min, then place in a reaction vessel and react at 170℃ for 12h. After the reaction, centrifuge and wash the sample, then dry it in a 70℃ oven for 12h to obtain MOF-high entropy sulfide precursor.
[0069] 2. Weigh 30 mg of MOF-high entropy sulfide precursor and 40 mg of thioacetamide, dissolve them in 20 ml of anhydrous ethanol, stir at room temperature for 30 min on a magnetic stirrer, then put them into a reaction vessel and react at 160 °C for 8 h. After the reaction is completed, centrifuge and wash the sample, and dry it in a 70 °C oven for 12 h to obtain the high entropy sulfide electrocatalyst ((FeCoNiZnMn)3S4).
[0070] Comparative Example 2
[0071] 1. Add 0.202g Fe(NO3)3·9H2O, 0.1487g Zn(NO3)2·6H2O, 0.1456g Co(NO3)2·6H2O, 0.145g Ni(NO3)2·6H2O and 0.128g Mg(NO3)2·6H2O to a beaker, then add 80ml isopropanol and 10ml glycerol, stir at room temperature for 40min, then place in a reaction vessel and react at 180℃ for 18h. After the reaction is completed, centrifuge and wash the sample, then dry it in a 70℃ oven for 12h to obtain the high-entropy sulfide precursor.
[0072] 2. Weigh 30 mg of high-entropy sulfide precursor and 40 mg of thioacetamide, dissolve them in 20 ml of anhydrous ethanol, stir at room temperature for 30 min on a magnetic stirrer, then put them into a reaction vessel and react at 160 °C for 18 h. After the reaction is completed, centrifuge and wash the sample, and dry it in a 70 °C oven for 12 h to obtain the high-entropy sulfide electrocatalyst ((FeCoNiZnMg)3S4).
[0073] Comparative Example 3
[0074] 1. Weigh 0.728g Co(NO3)2·6H2O and add it to a beaker. Then add 80ml isopropanol and 10ml glycerol. Stir at room temperature for 40min. Then place it in a reaction vessel and react at 180℃ for 18h. After the reaction is complete, centrifuge and wash the sample. Then place it in a 70℃ oven and dry for 12h to obtain the Co3S4 precursor.
[0075] 2. Weigh 30 mg of Co3S4 precursor and 40 mg of thioacetamide and dissolve them in 20 ml of anhydrous ethanol. Stir the mixture on a magnetic stirrer at room temperature for 30 min. Then, place it in a reaction vessel and react at 160 °C for 18 h. After the reaction is complete, centrifuge and wash the sample, and dry it in a 70 °C oven for 12 h to obtain Co3S4.
[0076] Comparative Example 4
[0077] 1. Weigh 0.337g Fe(NO3)3·9H2O, 0.248g Zn(NO3)2·6H2O, and 0.243g Co(NO3)2·6H2O and add them to a beaker. Then add 80ml isopropanol and 10ml glycerol. Stir at room temperature for 40min. Then place the mixture in a reaction vessel and react at 180℃ for 18h. After the reaction is complete, centrifuge and wash the sample. Then dry it in a 70℃ oven for 12h to obtain the (FeCoZn)3S4 precursor.
[0078] 2. Weigh 30 mg of (FeCoZn)3S4 precursor and 40 mg of thioacetamide, dissolve them in 20 ml of anhydrous ethanol, stir at room temperature for 30 min on a magnetic stirrer, then put them into a reaction vessel and react at 160 °C for 18 h. After the reaction is complete, centrifuge and wash the sample, and dry it in a 70 °C oven for 12 h to obtain (FeCoZn)3S4.
[0079] Application Example 1
[0080] 80 mg of the high-entropy sulfide electrocatalyst from Example 1 and 1.3 ml of LA133 binder were mixed evenly to obtain a coating slurry. The coating slurry was then uniformly coated onto one surface of a polypropylene separator to obtain a high-entropy sulfide electrocatalyst modified battery separator ((FeCoNiZnMn)3S4 / PP) with a coating thickness of approximately 25 μm.
[0081] Application Example 2
[0082] 80 mg of modifier and 1.3 ml of LA133 binder were mixed evenly to obtain a coating slurry. The coating slurry was then uniformly coated onto one surface of a polypropylene separator to obtain a modified battery separator with a coating thickness of approximately 25 μm. The modifiers were the high-entropy sulfide electrocatalysts of Examples 2-6 and the products prepared in Comparative Examples 1-4, respectively.
[0083] Verification Example
[0084] 1. Folding and bending experiment
[0085] The modified battery separators prepared in Application Examples 1 and 2 were subjected to bending and folding experiments. The method was as follows: the coated modified battery separator was cut into circular pieces with a diameter of 18 mm using a punching machine, then folded twice in succession, and then opened to restore the original shape. The powder shedding was observed.
[0086] Among them, the photographs of the folding process of the battery separator modified by the high-entropy sulfide electrocatalyst in Example 1 are as follows: Figure 3 As shown, no powder fell off after bending and folding, indicating that the high-entropy sulfide electrocatalyst modified battery separator has excellent mechanical properties and stability.
[0087] The bending and folding test results of other modified battery separators are shown in Table 1 below:
[0088] Table 1
[0089] Example 1 No powder shedding was observed. Example 2 Slight powder shedding occurred. Example 3 Slight powder shedding occurred. Example 4 Slight powder shedding occurred. Example 5 Slight powder shedding occurred. Example 6 Slight powder shedding occurred. Comparative Example 1 Severe powder shedding occurred. Comparative Example 2 Severe powder shedding occurred. Comparative Example 3 Severe powder shedding occurred. Comparative Example 4 Severe powder shedding occurred.
[0090] 2. Discharge specific capacity and rate performance experiments of lithium-sulfur batteries
[0091] 2.1 Preparation of carbon-sulfur positive electrode sheet:
[0092] Sulfur powder and BP2000 carbon black were ground at a mass ratio of 7:3 for 30 minutes, and then placed in an oven at 155℃ for 12 hours to obtain sulfur-carbon cathode material. The sulfur-carbon cathode material, conductive carbon, and LA133 binder were mixed and ground evenly at a mass ratio of 7:2:1. The slurry was then coated onto the surface of carbon-coated aluminum foil, vacuum dried at 60℃, and cut into round pieces with a diameter of 8mm to obtain sulfur-carbon electrode sheets.
[0093] 2.2 Preparation of lithium-sulfur batteries:
[0094] Assemble a 2032 button-type lithium-sulfur battery. A sulfur-carbon positive electrode sheet (8 mm diameter) was used as the positive electrode, a lithium sheet (16 mm diameter) as the negative electrode, and the modified battery separator (18 mm diameter) prepared in Application Examples 1 and 2 was used as the separator. The electrolyte composition was: 1 M bis(trifluoromethanesulfonyl)imide lithium, 2 wt% anhydrous lithium nitrate, with the solvent making up the balance. The solvent was a mixture of 1,3-dioxolane (DOL) and dimethyl ethylene glycol (DME) in a 1:1 volume ratio. A pure polypropylene separator (18 mm diameter) without any modification was used as a control.
[0095] 2.3 Electrochemical performance testing
[0096] The electrochemical performance of different lithium-sulfur batteries was evaluated and compared by performing constant current charge-discharge tests (test voltage range 1.7-2.8V, current density 0.2C) on a blue electric system. The test results are shown in Table 2. As can be seen from Table 2, the lithium-sulfur battery using the (FeCoNiMnZn)3S4 / PP separator achieved a first-cycle discharge capacity of 1341.5 mAh / g at a current density of 0.2C, showing a significant increase in discharge capacity. This indicates that the dopants in the high-entropy sulfide catalyst exhibit a synergistic effect, significantly catalyzing the redox reaction of sulfur. Compared to the batteries in Examples 2-6 and Comparative Examples 1-4, the battery with the (FeCoNiMnZn)3S4 / PP separator has the highest discharge specific capacity.
[0097] Table 2. Discharge specific capacity (mAh / g) of different batteries at 0.2C
[0098]
[0099] Rate performance was studied by applying different current densities, such as Figure 4The figures show the discharge specific capacities of the lithium-sulfur battery using the (FeCoNiMnZn)3S4 / PP separator from Application Example 1 at rates of 0.3C, 0.4C, 0.5C, 1C, and 2C, which are 1144 mAh / g, 880 mAh / g, 770 mAh / g, 680 mAh / g, and 562 mAh / g, respectively. When the rate returns to 0.4C, the specific capacity still reaches 783 mAh / g, with a decrease of only 11% at 0.4C. This indicates that the battery using a high-entropy sulfide catalyst to modify the separator has excellent capacity reversibility.
[0100] The above experiments clearly demonstrate that the active components in the high-entropy sulfide electrocatalyst modified membrane of this invention exhibit synergistic effects, effectively resisting polysulfides and enhancing the catalytic conversion ability of polysulfides, thereby improving sulfur utilization and enhancing the discharge specific capacity and cycle stability of lithium-sulfur batteries.
[0101] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, not all embodiments. Other embodiments can be obtained based on these embodiments without creative intent, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a high-entropy sulfide electrocatalyst, characterized in that... Includes the following steps: (1) Add at least 5 transition metal salts to a mixture of glycerol and solvent, stir until homogeneous, and then subject the resulting mixture to a solvothermal reaction. After the reaction, collect the product to obtain a high-entropy sulfide precursor. (2) Mix the high-entropy sulfide precursor, thioacetamide and solvent, stir to obtain a suspension, carry out a solvothermal reaction of the suspension, and then collect the product to obtain the high-entropy sulfide electrocatalyst. In step (1), the transition metal is selected from at least 5 of Fe, Co, Ni, Zn, Cu, Mn, and V, and the molar ratio between each transition metal salt is between 1:1 and 1:1.
3. In step (1), the molar ratio of glycerol to the total amount of transition metal salt is 50-60:1; In step (2), the mass ratio of the high-entropy sulfide precursor to thioacetamide is 3:4-6; In step (1), the solvothermal reaction temperature is 170℃-200℃ and the reaction time is 17-20 hours; in step (2), the solvothermal reaction temperature is 150-170℃ and the reaction time is 17-20 hours.
2. The preparation method according to claim 1, characterized in that: In step (1), the transition metal is Fe, Co, Ni, Zn, or Mn.
3. The preparation method according to claim 1, characterized in that: In step (1), there are 5-7 types of transition metal salts.
4. The preparation method according to claim 3, characterized in that: In step (1), there are 5 types of transition metal salts.
5. The preparation method according to claim 1, 2 or 3, characterized in that: In step (1), the molar amounts of each transition metal salt are the same.
6. The preparation method according to claim 1 or 2, characterized in that: In step (1), the transition metal salt is a soluble salt of a transition metal.
7. The preparation method according to claim 1 or 2, characterized in that: In step (1), the transition metal salt is selected from the chloride and nitrate of the transition metal.
8. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the high-entropy sulfide precursor to thioacetamide is 3:
4.
9. A high-entropy sulfide electrocatalyst prepared according to any one of claims 1-8.
10. A modified battery separator, characterized in that: It includes a battery separator body, on which an electrocatalyst layer is coated, wherein the electrocatalyst layer contains the high-entropy sulfide electrocatalyst as described in claim 9.
11. The modified battery separator according to claim 10, characterized in that: The coating thickness of the electrocatalyst layer on the battery separator body is 5–50 μm.
12. The application of the high-entropy sulfide electrocatalyst according to claim 9 in lithium-sulfur batteries.
13. The application of the modified battery separator according to claim 10 or 11 in lithium-sulfur batteries.
Citation Information
Patent Citations
Preparation method of high-entropy alloy used as lithium-sulfur battery catalytic material
CN115084527A
High-entropy compound for positive electrode of aluminum ion battery and preparation method of high-entropy compound
CN116169280A
